Pengaruh Kemandirian Belajar Terhadap Hasil Belajar Matematika Siswa Kelas XI Pada Materi Fungsi Komposisi di SMA Pelita Ngabang - Permia, Desi; Hermiati, Konstansia (Polinomial : Jurnal Pendidikan Matematika, 2025)
Interviews with mathematics teachers and a number of 11th grade students at SMA Pelita Ngabang showed that low student independence in learning had a direct effect on their mathematics learning outcomes. It was not uncommon for some 11th grade students to experience difficulties in solving composition function problems. This was due to a lack of independent learning strategies, a lack of student motivation to learn, and a lack of discipline in managing study time. In addition, students' dependence on explanations provided by teachers also contributes to suboptimal learning outcomes. This study aims to analyze the influence of independent learning on the mathematics learning outcomes of 11th grade students on the topic of composite functions at SMA Pelita Ngabang. The research approach applied uses a quantitative method with a correlational research design. Sampling was conducted using purposive sampling, while data collection was carried out through the distribution of questionnaires and exam questions. Data processing techniques in this study included validity testing, reliability testing, descriptive statistical analysis, normality testing, linearity testing, homogeneity testing, and simple linear regression testing. The results of statistical analysis using SPSS version 25 software show that the hypothesis test with the F test produced a significance value of 0.003, which is less than 0.05. In addition, the R Square coefficient of determination showed a value of 0.331, indicating that independent learning has a significant effect on mathematics learning outcomes of 33.1%, which is classified as moderate.